2015
DOI: 10.1080/13562517.2015.1101680
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Courses: designing for the unknown learner

Abstract: University teachers are faced with a problem of 'knowing' their learners when teaching on a Massive Open Online Course (MOOC). This paper explores and analyses what the University of Edinburgh has come to know about its recent MOOC participants, highlighting one particular course. We draw attention to barriers and enablers from coexistent understandings and expectations of course design, and from an abundance of highly-qualified participants. We compare characteristics of participants who report a positive exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Croft & Brown (2020) suggested that a lack of racial and cultural diversity amongst higher education faculty could perpetuate implicit biases within their online courses, because they base their assumptions about online learners on personal experience, believing them to hold the same kinds of privileges that they have themselves. Within the MOOC environment, faculty are designing for undefined audiences and may view them as a homogenous group (Macleod et al, 2016).…”
Section: Impact Of Designing For Equity and Inclusion On Learningmentioning
confidence: 99%
“…Croft & Brown (2020) suggested that a lack of racial and cultural diversity amongst higher education faculty could perpetuate implicit biases within their online courses, because they base their assumptions about online learners on personal experience, believing them to hold the same kinds of privileges that they have themselves. Within the MOOC environment, faculty are designing for undefined audiences and may view them as a homogenous group (Macleod et al, 2016).…”
Section: Impact Of Designing For Equity and Inclusion On Learningmentioning
confidence: 99%
“…For instance, while Christensen et al (2013) and Despujol et al (2014) revealed that 56.9% and 56% (respectively) of their respondents were male, Morris et al (2015) and Bayeck (2016) on the other hand found women to represent respectively 59.83% and 60% of learners in their courses. Therefore, as MacLeod et al (2016) indicate, it may not be a good idea to make general claims about gender distribution, as the latter may vary depending on the contents of the course. Courses whose contents are appealing to the male population (due to social factors that go beyond the scope of this paper) would likely attract more males, and the other way around.…”
Section: Profiles Of Mooc Participantsmentioning
confidence: 99%
“…All in all, this research has made us understand that EFL MOOCs are not very different from MOOCs in general with regard to their tendency to attract university graduates and adults. In addition, it has consolidated the belief that making general claims regarding gender might not be a good idea (MacLeod et al, 2016).…”
Section: Efl Mooc Vs Mooc Demographics (Rq1)mentioning
confidence: 99%
“…By adopting a pedagogical perspective, MOOCs represent the virtuous integration of two growing trends: the online learning, which has been important since the beginning of twenty-first century (Butcher & Wilson-Strydom, 2013), and the Open Educational Resources (Yuan & Powell, 2013), which include learning content, tools and implementation resources (Hylén, 2006;Pawlowski & Bick, 2012). Further, the diffusion of MOOCs allows setting up new educational approaches and design methods for on line courses, as widely discussed in the literature (Macleod, Sinclair, Haywood, & Woodgate, 2016).…”
Section: Principles and Approaches For Mooc Design And Evaluationmentioning
confidence: 99%
“…These courses can transform training by giving excellent choices for free education without any boundaries (Peters & Seruga, 2016). Indeed, the openness of MOOC-based programs favours the democratization (DeWaard et al, 2011) and commodification of education (Macleod, Sinclair, Haywood, & Woodgate, 2016), even if this does not imply that contents do not have to be well organized (Laurillard, 2014).…”
Section: Introductionmentioning
confidence: 99%